Mapping Organic Farming Occupations: Bridging Competency Gaps and Addressing Generational Challenges - Surono Surono (Journal Research of Social Science, Economics, and Management, 2025)
This This research aims to address the gap between the competencies required by the organic farming sector and the skills provided by educational institutions in Indonesia. By mapping occupations within the Indonesian Qualification Framework (IQF) and using the Rapid Assessment Process (RAP) along with the Regional Model Competency Standard (RMCS), the study identifies key roles and competencies necessary for the industry, ranging from entry-level workers to advanced specialists. The findings suggest that current curricula fail to integrate advanced technologies and practical skills training needed in organic farming. The study proposes curriculum enhancements that incorporate sustainable farming practices, biochar technology, and entrepreneurial education to align with industry demands. A strategic framework is also introduced to address the generational gap in the sector by modernizing the perception of farming and attracting younger talent through digital engagement and innovative educational approaches. The research highlights the importance of bridging the competency gap and fostering a skilled workforce capable of driving sustainable agricultural practices, ultimately strengthening the organic farming sector and ensuring its long-term viability.